Implementation of Religious Moderation Values in Teaching Materials at NWDI Middle School and Muhammadiyah Middle School - Abubakar, Mujahidin; Nasir, M. Abdun; Mukhtar, Fathurrahman; Ilham, Budi (Journal of English Language and Education, 2025)
This study was conducted at Muhammadiyah Narmada Junior High School and Al-Kamal IT NWDI Junior High School. The purpose of this research is to analyze the implementation of religious moderation values in the teaching materials of both schools. Employing a qualitative case study approach, data were collected through observation, interviews, and documentation from school principals, Muhammadiyah teachers, NWDI teachers, and students. The data analysis involved data reduction, presentation, and conclusion drawing. The findings indicate that SMP IT Al-Kamal NWDI implements religious moderation through several strategies: (1) instilling Islamic beliefs aligned with Ahlussunnah waljama'ah understanding; (2) assigning leadership tasks to students as a form of learning; (3) habituating students through school or boarding school programs; and (4) fostering a sense of love for the nation and state.